2019
DOI: 10.1111/his.13929
|View full text |Cite
|
Sign up to set email alerts
|

Actinomyces in Crohn’s‐like appendicitis

Abstract: Aims Appendicitis with a Crohn’s‐like histological appearance generally raises concern for Crohn’s disease, Yersinia infection, and interval appendectomy. Actinomyces infection is a recognised cause of chronic appendicitis that can histologically mimic Crohn’s disease. Methods and results We report on 20 cases of appendicitis with Crohn’s‐like histological features that were due to Actinomyces. Most patients presented with acute or chronic abdominal pain. Imaging studies suggested a mass in five cases. Two pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Sally A Cross reported that Desulfovibrio can cause bacteremia ( 41 ). Besides, Actinomyces are normal members in human gut and can cause endogenous infection, which is a well-recognized cause of chronic appendicitis, and histologically mimicking Crohn’s disease ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sally A Cross reported that Desulfovibrio can cause bacteremia ( 41 ). Besides, Actinomyces are normal members in human gut and can cause endogenous infection, which is a well-recognized cause of chronic appendicitis, and histologically mimicking Crohn’s disease ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…10 A few subsequent studies have reported additional features that could be seen in IA, including Actinomyces infection, pulse granulomas and postinflammatory mucosal hyperplasia. [11][12][13] Whereas, in the past, most appendectomy specimens in our practice demonstrated AA, we have noted an increase in IA in recent years. We often receive appendectomy specimens with a provided clinical history of acute appendicitis on the requisition form, without specific information regarding prior supportive therapy, and sometimes additional information is not readily available in the patient's medical record.…”
Section: Introductionmentioning
confidence: 52%
“…(Interestingly, a recent study in a paediatric cohort primarily observed serosal granulomas in IA 19 20 such as with Enterobius vermicularis 21 or Actinomyces spp., 11 both of which can be observed in the appendiceal lumen. The most common infectious organism causing granulomatous appendicitis is Yersinia spp 22 …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Actinomycetes are recognized to be a cause of chronic appendicitis. Actinomycetes are also associated with Crohn-like appendicitis with significant fibrosis, transmural inflammation, lymphoid hyperplasia, and granuloma[ 29 ]. TM7x is a saccharifying bacteria, which is a parasitic bacterium that interacts with core members of Actinomycetes.…”
Section: Discussionmentioning
confidence: 99%